Fenomena Pembelajaran Musik Online: Antara Tren dan Tantangan - Bagaskara, Akbar; Rokhani, Umilia; Widodo, Tri Wahyu (Universitas Indraprasta PGRI Jakarta, 2024)
This article is written to reveal; trends in online music learning, innovations in online music curriculum, challenges in online music learning, issues of teaching quality and evaluation of online music learning, and the success of online music learning programs. The method used in this research is qualitative type, using data analysis of Miles and Huberman's theory which consists of four pillars namely; data collection, data reduction, data presentation, and conclusion. The results of this study show; (1) Trends in online music learning have a good impact in creating exciting opportunities for music learning, as well as presenting new ways of understanding and creating musical works. (2) Innovations in the online music learning curriculum form a new culture in music teaching, this can be seen from the use of the cloud as a shared archive service to access every material and upload assignments, the presence of collage music features that facilitate remote music collaboration for students, and the emergence of digital music applications, making music learning more efficient. (3) Problems or challenges that arise in online music learning are generally caused by poor internet connection. As a result, the music learning that is delivered becomes intermittent. (4) teaching quality issues and evaluation problems of online music learning can be described as follows, the uneven ability of teachers who master the features of online music learning and at the evaluation stage, the potential for cheating can certainly occur, especially with the limitations of monitoring students' activities during the learning process. (5) in general, online music learning is dominantly effective and successful, this can be traced from other supporting research.